Development, and evaluation of drug monitoring system for multiple sclerosis patients - Reza Safdari; Abdorreza Naser Moghadasi; Sahar Khenarinezhad; Ehsan GhazanfariSavadkoohi (Tehran University of Medical Sciences, 2021)
Background and Aim: Taking a wide range of medications in Multiple sclerosis (MS) patients can lead to side effects and drug interactions. Therefore, the use of intelligent systems such as drug monitoring systems can help in the effective and timely treatment of MS disease. In this regard, the present study was conducted to design, development, and evaluation of the drug monitoring system for multiple sclerosis patients. Materials and Methods: The present descriptive-developmental study was performed in four stages. In the first stage, by searching the library resources and valid guidelines, the minimum data set was determined and provided to neurologists and MS fellowships in the form of checklists for validation. Then the software was designed logically and coded based on the opinion of experts. In the last stage, the software was evaluated by end-users. Results: The information elements in the software design were categorized into patient demographic information, medical history, clinical signs, imaging procedures, laboratory tests for ocrelizumab and fingolimod drugs, counseling, and treatment data. Finally, the performance of the drug monitoring system was evaluated with an average of 7.9 and was approved by users. Conclusion: The results of software evaluation showed that the drug monitoring system can help general practitioners, neurologists, and MS fellowships in monitoring and follow-up of patients and lead to increased patient safety.